An Investigation of Defected Ground Structure Effect on Bandwidth Enhancement of U-Shape Microstrip Antenna for Small Ultra Wide-Band Radar Device - Dina Puspa Wulandari; Heroe Wijayanto; Edwar Edwar (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2019)
Ultra-wideband radar has been widely used for various purposes, including detection of human vital signs, small displacement detection, and ground penetrating radar. In order to work properly, it requires an antenna with a wide bandwidth. This study reports an investigation of a bandwidth enhancement method by combining the U-shaped microstrip patch antenna with the Defect Ground Structure (DGS). In this research, the antennas are operated at 5.8 GHz. The results show the combination of U-shaped patch and DGS produce twice bandwidth performance compared to the one without DGS. In our study the diamond shape DGS gives the best performance among various DGS structures.